Coeliac Disease: A Subtle yet Life Changing Diagnosis - Dilhara Karunaratne MBChB (Hons), BSc (Hons), MRCS, PGCME (Journal of Patient Experience, 2021)
Coeliac disease is a common autoimmune condition, which may present with a wide variety of extraintestinal symptoms that contribute to a significant delay in disease diagnosis. This personal account, from the perspective of a medical doctor, is an insight into the lived experience of coeliac disease, the process of diagnosis, and the lifestyle changes and challenges associated with the gluten-free diet.